Psychoeducational Challenges in Spanish Children With Dyslexia and Their Parents’ Stress During the COVID-19 Pandemic - Soriano-Ferrer, Manuel; Morte-Soriano, Manuel Ramón; Begeny, John; Piedra-Martínez, Elisa (Frontiers in Psychology, 2021)
Background: To our knowledge, no currently available studies have looked specifically at the impact of COVID-19 on students with dyslexia and their families. Research on this topic is needed to offer greater support for this population of students and their families. Objective: The main objective of this paper is to examine the psychoeducational impact of the required COVID-19 quarantine in Spain among children with dyslexia and their families. Method: A sample of 32 children with dyslexia and their mothers participated in this study. Measures: Children and adolescents with dyslexia and their mother completed several measures before the quarantine in Spain and again during the quarantine. Children completed measures of depression, state anxiety, reading activity, and reading motivation. Mothers provided demographic information and completed measures related to students’ emotional and behavioral difficulties as well as parenting stress, parental distress, and a questionnaire about psychoeducational problems during quarantine. Results: Major findings showed that during quarantine, children with dyslexia had increased levels of depression and anxiety symptoms, and parents perceived their children as having more emotional symptoms, hyperactivity-inattention, and conduct problems. During quarantine, children and adolescents with dyslexia also showed less reading activity and less reading motivation. Parents also reported significantly more stress, during quarantine compared to pre-quarantine conditions. Some demographic and psychological variables predicted children´s wellbeing as well parental stress. The questionnaire related to impacts of quarantine also revealed several important findings. For example, nearly all parents of children with dyslexia reported (a) difficulties in establishing study routines, (b) that the quarantine negatively affected their child's learning, and (c) that they did not receive sufficient help from teachers on how to support their child’s learning. Conclusion: This study offers a preliminary investigation into this topic and elucidates several psychoeducational challenges that children with dyslexia and their families have experienced during the quarantine in Spain. Study findings highlight the need to provide immediate support for children with dyslexia and emphasizes the importance of developing prevention programs to mitigate any future negative impacts of COVID-19 on children with dyslexia and their parents.